Reimplante dentário após o preenchimento do canal com pasta de β-glicerofosfato de cálcio ou pasta de hidróxido de cálcio + MTA estudo histomorfométrico em ratos - Silva, Pedro Ivo Santos [UNESP] (2013)
Thooth avulsion mainly affects young patients who have incomplete root formation, with frequent necrotic pulp and apexification impaired. The large foramen hinders the insertion of dressings delay. The use of a long time fill to facilitate control of formation and resorption of mineralized tissue barrier permitting the apical seal. Calcium hydroxide and MTA has been the most widely used material for this purpose. The objective of this work is to study the repair process of rat incisors with dental elements reimplanted late after root canal filling with paste β-glycerophosphate calcium or calcium hydroxide paste. Were used 30 male rats were divided into 3 groups of 10 animals. All the teeth were extracted and kept in dry for 60 minutes. In Group I, the root canals were filled with saline. Group II used the paste of calcium hydroxide and finished with a MTA plug and Group III were used β-glycerophosphate calcium paste. The teeth were reimplanted and euthanasia was performed 60 days later for histomorfometric analyse with HE(Hematoxiciline-Eosine). Results showed that the groups I and III were more impaired by inflammatory root resorption than group II. Group II had less involvement by total reabsorption of the group II (p <0,05). In groups I and III, the periapical region showed the greatest extent of fibrous connective tissue with inflammatory infiltrate. It is concluded that β-glycerophosphate calcium were less effective than calcium hydroxide in the control of root resorption and repair of the periapical area of mineralized tissue.